1999
DOI: 10.1002/(sici)1097-4644(19991201)75:3<437::aid-jcb9>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protein phosphatase activity by regucalcin localization in rat liver nuclei

Abstract: The regulatory role of regucalcin on protein phosphatase activity in isolated rat liver nuclei was investigated. Phosphatase activity toward phosphotyrosine and phosphoserine was significantly increased by the addition of CaCl(2) (10(-5) and 10(-4) M) in the enzyme reaction mixture. Trifluoperazine (25 and 50 microM), an antagonist of calmodulin, significantly inhibited protein phosphatase activity toward phosphoserine, while it had no effect on the enzyme activity toward phosphotysine and phosphothreonine. Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…An earlier study reported that regucalcin is secreted, at significant concentrations, into buffalo seminal vesicular fluid (Harikrishna et al, ), yet we did not detect this protein in the seminal plasma separated from ejaculated semen. One possible reason for this may be its transfer from seminal plasma to spermatozoa, which is consistent with the reported translocation of exogenous regucalcin to the nucleus of osteoblasts (Otomo and Yamaguchi, ) and liver cells (Omura and Yamaguchi, ), where it alters gene expression and modulates enzyme activity. Another possibility is that the regucalcin was diluted to undetectable levels— although we failed to detect a band even after probing higher total volumes of seminal plasma.…”
Section: Discussionsupporting
confidence: 80%
“…An earlier study reported that regucalcin is secreted, at significant concentrations, into buffalo seminal vesicular fluid (Harikrishna et al, ), yet we did not detect this protein in the seminal plasma separated from ejaculated semen. One possible reason for this may be its transfer from seminal plasma to spermatozoa, which is consistent with the reported translocation of exogenous regucalcin to the nucleus of osteoblasts (Otomo and Yamaguchi, ) and liver cells (Omura and Yamaguchi, ), where it alters gene expression and modulates enzyme activity. Another possibility is that the regucalcin was diluted to undetectable levels— although we failed to detect a band even after probing higher total volumes of seminal plasma.…”
Section: Discussionsupporting
confidence: 80%
“…Regucalcin plays a role in maintaining intracellular Ca 2+ homeostasis, the inhibitory regulation of various Ca 2+dependent protein kinases and tyrosine kinases, protein phosphatases, nitric oxide synthase, and the control of the enhancement of protein synthesis, nuclear deoxyribonucleic acid (DNA) and RNA synthesis in proliferative cells (6)(7)(8)(18)(19)(20)(21)(22)(23)(24)(25). Recent study has demonstrated that regucalcin has suppressive effects on cell proliferation and apoptosis, which are mediated through many signaling factors, in cloned rat hepatoma H4-II-E cells and normal rat kidney proximal tubular epithelial NRK52E cells overexpressing regucalcin (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of RGN mRNA suggests the possibility of RGN protein synthesis either in germ cells or spermatozoa or in both. Another possibility is by translocation of RGN into spermatozoa from the external source as it has been detected in the secretions of male reproductive tract (Harikrishna, Shende, Reena, et al., ; Laurentino et al., ), and there are reports of translocation of exogenous RGN to the nucleus of osteoblasts (Otomo & Yamaguchi, ) and liver cells (Omura & Yamaguchi, ). Further studies are needed to investigate whether the RGN associated with spermatozoa is of endogenous origin only or both endogenous and exogenous origin.…”
Section: Discussionmentioning
confidence: 99%